PENERAPAN TEKNOLOGI PENYIRAM TANAMAN OTOMATIS BERBASIS WEBCAM UNTUK USAHA TANAMAN “SURYA NURSERY" DI KELURAHAN PEDALANGAN SEMARANG: PENERAPAN TEKNOLOGI PENYIRAM TANAMAN OTOMATIS BERBASIS WEBCAM UNTUK USAHA TANAMAN “SURYA NURSERY" DI KELURAHAN PEDALANGAN SEMARANG - Sayekti, Ilham; Aji, Achmad Fahrul; Adiwismono, Agus; Rochadi, Agus; Supriyo, Bambang; Krishna, Bangun; Utomo, Kusno; Nursaputro, Septiantar Tebe; Kusumastuti, Sri; Kartika, Vinda Setya (Bangun Rekaprima, 2025)
This community service activity aims to help the ornamental plant business at "Surya Nursery," located in Pedalangan Village, Semarang, overcome plant care constraints due to limited time and human resources. The technology applied is an Arduino UNO-based automatic plant waterer equipped with a webcam for real-time monitoring in the business environment. The watering tool consists of 5 sprinklers that can rotate 360 degrees for an area of 200 square meters and can operate automatically or manually depending on the needs of the partner.Through this program, the team provides training and assistance to business partners, starting from device installation, system use, and maintenance of the technology applied. This system is expected to increase time efficiency, reduce water consumption, and maintain plant quality consistently.The results of this activity show that the tool can operate well, and partners feel the benefits in the form of increased productivity and reduced daily workload. The technology applied also opens up opportunities for "Surya Nursery" to increase competitiveness in the ornamental plant market. With this program, it is hoped that similar technology can be adopted by other small and medium enterprises in the agricultural sector.